Workplaces Disrupted: Exploring The Psychological Well-Being in Egyptian Office Spaces Post-COVID - Raafat, Mirna (AUC Knowledge Fountain, 2023)
Triggered by public concerns over office workplace physicality after the COVID-19 pandemic, this research sheds the light on the expected future office space redesign in relation to the employees’ emergent habits while working from home. The purpose of this study is to assess the latest working experience which took place outside of its normal habitat and is supposed to change the trajectory of office design. Therefore, this research provides a better understanding of the emergent habits caused by the long-term lockdown of the pandemic and the modifications expected to take place in the post-COVID-19 offices to suit the stakeholder’s needs. Two methods are used for the research process a macro-scale investigation of an online survey targeting Egyptian employees who worked at least one month from home and a micro-scale method consist of ethnographic fieldwork in 5 Egyptian offices located in Cairo. The extracted data was analyzed using statistical analysis for the survey and thematic analysis for the ethnographic interviews. The results revealed the future office spaces will need to be designed as being a ‘home for work’ which work as a destination for the employees rather than a location. In some studied areas, some physical alterations were depicted, however they were not sufficient for to ameliorate the employees’ experience and improve their well-being. Which highlighted that the real transformation needs to be in the managerial mindsets not only in the simplistic physical alterations. The managers’ standing point need to complement their employee’s new perception of the working process. The latest studies conducted in Egypt mainly focused on the employees’ productivity level and psychological wellbeing at home, therefore, this research is valuable for the physical design of the future office spaces and the results will contribute to the architects and the local organizations in binding some criteria which can ameliorate the office environment for the sake of the employees’ psychological wellbeing.